A Comparison of Economic Impact Measurement Techniques for a Tourism Special Event. (May 2017) - Warnick, Rodney B.; Bojanic, David C.; Cartier, Elizabeth
The study's purpose was to examine and update the research methods and measurement issues associated with assessing the economic impact (EI) of an extended duration, regional tourism event. Specifically examined were the issues with the implementation of EI studies in regard to further testing and re-verifying the methods used in (1) measuring a representative sample from an information-seeking/sharing web site and social media registration and engagement lists; (2) comparing locals and nonlocals within a region using different definition techniques; (3) examining the impact of VFRs within the local markets; and (4) comparing the estimation of purchasing within versus outside an impact area. Recommendations for further analysis and implementation for EI studies and the management of tourism special events are presented.